Oral Health Education and Prevention Project: an experience report from a school on Cotijuba-PA Island, Brazil (Research, Society and Development, 2023)
Oral health is essential for basic activities such as speaking, eating, smiling, showing emotions, among others. If these basic abilities are affected, this directly interferes with self-esteem, well-being and general health, which can lead to poor performance and school attendance. From the perspective of the authors, there was a need for actions related to oral health, as well as a topic for discussion and contextualization in the school environment. Here we report on the educational practice carried out in the 'Oral Health Education and Prevention' project, the aim of which was to promote oral health in a school on the island of Cotijuba, PA. The method used in this work was the Experience Report. Pedagogical practices were developed in which students were able to strengthen the culture of oral health care, among them: storytelling, conversation circles, dynamics involving oral health habits and care, and the culmination of the project was supervised tooth brushing. The themes related to Oral Health Education were discussed in the classroom, giving the students a broader knowledge of oral health. The actions carried out are fundamental for education in habits that are beneficial to collective oral health, contributing to the dialog about basic health care for disease prevention.